Designing and Optimizing Heat Storage of a Solar-Assisted Ground Source Heat Pump System in China. (24th February 2020) - Gao, Yan; Sun, Zhi; Lin, Xinxing; Wang, Chuang; Sun, Zongyu; Chen, Yanhong
Abstract : The cold accumulation problem can lead to performance degradation of heat pumps. This paper presents the design and optimization of a solar-assisted storage system to solve this issue. A ground source heat pump (GSHP) project was established using the transient system simulation program (TRNSYS) based on a ground heat exchange theoretical model, which was validated by a previously established experiment in Beijing. The Beijing, Harbin, and Zhengzhou regions were used in numerical simulations to represent three typical cities where buildings require space heating (a cold region, a severe cold region, and a hot summer and cold winter region, respectively). System performance was simulated over periods of ten years. The simulation results showed that the imbalance efficiencies in the Beijing, Harbin, and Zhengzhou regions are 55%, 79%, and 38%, respectively. The annual average soil temperature decreases 7.3°C, 11.0°C, and 5.3°C during ten years of conventional GSHP operation in the Beijing, Harbin, and Zhengzhou regions, respectively. Because of the soil temperature decrease, the minimum heating coefficient of performance (COP) values decrease by 23%, 46%, and 11% over the ten years for GSHP operation in these three regions, respectively. Moreover, the simulation data show that the soil temperature would still be decreasing if based on the previous solar energy area calculation method. Design parameters such as the solar collector size are optimized for the building load and average soil temperature in various cold regions. Long-term operation will test the matching rate of the compensation system with the conventional GSHP system. After the system is optimized, the solar collector area increases of 20% in the Beijing region, 25% in the Harbin region, and 15% in the Zhengzhou region could help to maintain the annual average soil temperature balance. The optimized system could maintain a higher annual average COP because of the steady soil temperature. It provides a method for the design of a solar collector area which needs to be determined in the seasonal heat storage solar ground source heat pump system.